Music therapy applied to complex blast injury in interdisciplinary care: a case report. Issue 19 (11th September 2019) - Vaudreuil, Rebecca; Avila, Luis; Bradt, Joke; Pasquina, Paul
Abstract: Purpose: Music therapy has a long history of treating the physiological, psychological, and neurological injuries of war. Recently, there has been an increase in the use of music therapy and other creative arts therapies in the care of combat injured service members returning to the United States from Iraq and Afghanistan, especially those with complex blast-related injuries. This case report describes the role of music therapy in the interdisciplinary rehabilitation of a severely injured service member. Methods: Music therapy was provided as stand-alone treatment and in co-treatment with speech language pathology, physical therapy, and occupational therapy. The report is based on clinical notes, self-reports by the patient and his wife, and interviews with rehabilitation team members. Results: In collaboration with other treatment disciplines, music therapy contributed to improvements in range of motion, functional use of bilateral upper extremities, strength endurance, breath support, articulation, task-attention, compensatory strategies, social integration, quality of life, and overall motivation in the recovery process. The inclusion of music therapy in rehabilitation was highly valued by the patient, his family, and the treatment team. Conclusions: Music therapy has optimized the rehabilitation of a service member through assisting the recovery process on a continuum from clinic to community. Implications for Rehabilitation: Music therapy in stand-alone sessions and in co-treatment with traditional disciplines can enhance treatment outcomes in functional domains of motor, speech, cognition, social integration, and quality of life for military populations. Music therapists can help ease discomfort and difficulty associated with rehabilitation activities, thereby enhancing patient motivation and participation in interdisciplinary care. Music therapy assists treatment processes from clinic to community, making it highly valued by the patient, family, and interdisciplinary team members in military healthcare. Music therapy provides a platform to prevent social isolation by promoting community integration through music performance.